Nutritional Assessment of Patients with Type-2 Diabetes in a Tertiary Level Hospital in a Low-and Middle-income Country - Rama Subba; Asmita Luitel; Rinku Joshi; Bhupal Baniya (Journal of Karnali Academy of Health Sciences)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by higher blood glucose levels. It is a global public health burden. One of the major risk factors for developing diabetes is inadequate dietary knowledge in many diabetic patients. This study was carried out to understand the dietary patterns of diabetic patients along with other factors including compliance and clinical features so that effective interventions can be taken for proper management of disease.